'As Long as It's Used for Beneficial Things': An Investigation of non-Māori, Māori and Young People's Perceptions Regarding the Research use of the Aotearoa New Zealand Integrated Data Infrastructure (IDI). (October 2022) - Thabrew, Hiran; Aljawahiri, Noor; Kumar, Harshali; Bowden, Nicholas; Milne, Barry; Prictor, Megan; Jordan, Vanessa; Breedvelt, Josefein; Shepherd, Toni; Hetrick, Sarah
The Aotearoa New Zealand Integrated Data Infrastructure (IDI) is a national database containing a wide range of data about people and households. There is limited information about public views regarding its use for research. A qualitative study was undertaken to examine the views of forty individuals attending a large hospital in Auckland, including those of Māori ethnicity and young people. Semi-structured interview data were analysed using Braun and Clarke's method of thematic analysis. Seven key themes emerged: 1) Limited knowledge about medical data held in national databases; 2) Conditional support for the use of the IDI, including for research; 3) Concerns regarding the misuse of IDI data; 4) The importance of privacy; 5) Different views regarding consent for use of data for research; 6) Desire for access to personal data and the results of research; and 7) Concerns regarding third party and commercial use. Young people and those of Māori ethnicity were more wary of data misuse than others. Although there is reasonable support for the secondary use of public administrative data in the IDI for research, there is more work to be done to ensure ethical and culturally appropriate use of this data via improved consent privacy management processes and researcher training.